2016
DOI: 10.1021/acs.est.5b04618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gas-Phase Organics Using Proton Transfer Reaction Time-of-Flight Mass Spectrometry: Cooking Emissions

Abstract: Cooking processes produce gaseous and particle emissions that are potentially deleterious to human health. Using a highly controlled experimental setup involving a proton-transfer-reaction time-of-flight mass spectrometer (PTR-ToF-MS), we investigate the emission factors and the detailed chemical composition of gas phase emissions from a broad variety of cooking styles and techniques. A total of 95 experiments were conducted to characterize nonmethane organic gas (NMOG) emissions from boiling, charbroiling, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(157 citation statements)
references
References 49 publications
9
147
1
Order By: Relevance
“…Heating cooking oils, a fundamental process of frying, was found to produce large amounts of fine particulate matter (PM 2.5 ) (Torkmahalleh et al, 2012;Gao et al, 2013) and VOCs (Katragadda et al, 2010;Klein et al, 2016a). The PM 2.5 emission rate for peanut, canola, corn and olive oils heated at 197 • C was shown to be as high as 54 mg min −1 (Torkmahalleh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heating cooking oils, a fundamental process of frying, was found to produce large amounts of fine particulate matter (PM 2.5 ) (Torkmahalleh et al, 2012;Gao et al, 2013) and VOCs (Katragadda et al, 2010;Klein et al, 2016a). The PM 2.5 emission rate for peanut, canola, corn and olive oils heated at 197 • C was shown to be as high as 54 mg min −1 (Torkmahalleh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Schauer et al (2002) estimated that cooking seed oils might contribute a significant fraction of lighter n-alkanoic acids such as nonanoic acid in the atmosphere. The VOCs emitted from heated cooking oils were dominated by aldehydes (Klein et al, 2016a), which were suggested to be potential SOA precursors (Chacon-Madrid et al, 2010). Despite these previous efforts, there are still no available data regarding SOA formation from heated cooking oils.…”
Section: Introductionmentioning
confidence: 99%
“…Filters from cooking processes (frying, related largely to oil pyrolysis; Klein et al, 2016a;Allan et al, 2010) did not yield measurable mass spectra in our LDI-MS. This observation is in agreement with a prior study, which performed in situ single-particle LDI-MS measurements at 266 nm (using the ATOFMS) and did not observe cooking particles (Healy et al, 2013).…”
Section: Combustion-source Samplesmentioning
confidence: 84%
“…after simulated ageing in a smog chamber for 1 h (equivalent to an OH dose of 10 7 cm −3 h) and 4 h (OH dose 3×10 7 cm −3 h) (Bruns et al, 2015(Bruns et al, , 2016. Additionally, filter samples collected during cooking experiments were analysed (Klein et al, 2016a, b).…”
Section: Sample Collection and Other Chemical Analysesmentioning
confidence: 99%
“…Experiments were conducted in the atmospheric chamber of the Paul Scherrer Institute (PSI, Villigen, Switzerland) 15 (Platt et al, 2013;Klein et al, 2016). The full set-up and protocol of our experiments were already described in Bertrand et al (2017;.…”
Section: Methodsmentioning
confidence: 99%